Observation of the electroweak production of two same-sign W bosons in proton-proton collisions with the ATLAS detector - Mwewa, Chilufya (Department of Physics, 2020)
The production of same sign WW bosons (W±W±) is an extremely rare process predicted within the Standard Model (SM). It results from electroweak mediated processes such as Vector Boson Scattering (VBS), a process linked with electroweak symmetry breaking. Therefore, an observation of the W±W± VBS process does not only confirm the predictions of the SM at such a small cross-section, but it also provides an opportunity to test the electroweak sector and the Higgs mechanism. Evidence for this process was found, at a significance of 4.5 and 2.0 by the ATLAS and CMS experiments respectively, during Run I of the Large Hadron Collider (LHC). Following this potential for discovery, this search was repeated in Run II of the LHC. The CMS experiment reported an observation of this process at a significance of 5.5 in September 2017 while ATLAS reported it at a significance of 6.9 in July 2018. In ATLAS, the search was conducted by looking for events with two same sign leptons (e±e±, e± µ± and µ±µ± ), large missing transverse momentum (Emiss T ) and two forward jets using 36.1 fb1 of data collected at a proton-proton center of mass energy of 13 TeV in 2015 and 2016. This thesis presents an overview of the observation of this rare process by the ATLAS experiment while focussing on the study of backgrounds resulting from photon conversions as well as studies for the enhancement of the the VBS signal which were the student's primary contribution to the full analysis. In addition, the student's contribution to the ATLAS upgrade project is also highlighted.